Physiological basis of herbicide interaction and integrated management of Palmer amaranth (Amaranthus palmeri) - Cuvaca, Ivan Bernardo (Kansas State University, 2019)
Palmer amaranth is a major threat to many cropping systems in the USA. As a result of selection, Palmer amaranth has evolved resistance to at least six herbicide modes of action including microtubule-, 5-enolpyruvylshikimate-3-phosphate synthase-, acetolactate synthase-, photosystem II-, hydroxyphenylpyruvate dioxygenase-, and protoporphyrinogen oxidase- inhibitors. Dicamba is effective for Palmer amaranth control; however, extensive use of this herbicide increases the likelihood of evolution of resistance to dicamba. The overall objective of this dissertation was to investigate the physiological basis of interaction of herbicides with different modes of action in Palmer amaranth control and evaluate use of integrated approaches to manage Palmer amaranth in field conditions. The specific objectives were to: 1) evaluate the effect of plant height on dicamba efficacy to control Palmer amaranth; 2) investigate the mechanism of resistance to glyphosate in a Palmer amaranth accession from Kansas, and evaluate efficacy of glyphosate and dicamba tank-mix to control this accession; 3) investigate the physiological basis of glyphosate and dicamba interaction in tank-mix to control Palmer amaranth; 4) determine the efficacy of reduced dicamba use on Palmer amaranth control in irrigated corn production; and 5) investigate grain sorghum and Palmer amaranth growth and reproductive attributes in response to sorghum density and nitrogen rate under irrigated conditions. All experiments were repeated and appropriate statistical tests were used for data analyses. The results indicate: a) increased absorption and translocation of dicamba contribute to increased efficacy to control Palmer amaranth at early growth stage; b) tank mixing glyphosate and dicamba had a synergistic effect on Palmer amaranth control; c) rapid absorption of dicamba and increased translocation of glyphosate resulted in increased Palmer amaranth control when applied in combination; d) there is an opportunity to maintain grain yield while effectively controlling Palmer amaranth in irrigated corn with the integration of increased corn plant population density and reduced dicamba application and e) integrating sorghum plant population and nitrogen did not suppress Palmer amaranth in irrigated sorghum, although sorghum grain yield was maintained. The outcome of this dissertation provides several strategies to improve control of Palmer amaranth.
Keywords: Palmer amaranth; Dicamba; Resistance; Growth stage; Herbicide interaction; Integrated management